Design of Filter Using MOS Current Mode Logic - J Princy Joice; M Anitha; I Rexlin Sheeba (Institute of Advanced Engineering and Science, 2016)
MCML (MOS Current Mode Logic) is a method used for the purpose of reducing the delay and power of the circuit. In high speed application this method is used to reduce the power. In this method the sleep transistor is inserted in series with the supply voltage (or) current source to reduce the power. Different power gating techniques are been used to reduce the static power and to improve the speed and efficiency of the circuit. In this paper, the filter can be designed by using MCML logic. The fourth order band pass filter by using MCML logic is introduced. In order to reduce the power and delay this method is proposed.